ELABORASI KONSEP IQRA’ SEBAGAI PENGUATAN LITERASI UMAT DI ERA 4.0 - Alfian Sani (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
In the current 4.0 era, literacy is one of the most important things for a person's survival to study well and be educated. Some people are only able to read textually so that the level of reading starting from literacy, interpretive, critical and creative understanding has not been seen. Research Objectives: (1) To find out the views of mufasir in understanding iqra'; (2) To find out how to read the signs of the times in the 4.0 era? This study uses the thematic interpretation method with a conceptual analysis approach. The verses are collected on the same theme as the problem raised and analyzed in detail. The results of the study: (1) The view of the mufasir in understanding iqra' is fi'il amar (read command verb). (2) Reciting iqra' (reading) the signs of the times in the 4.0 era is urgently needed in order to educate people from being consumptive to a productive society.